2014
DOI: 10.1097/mat.0000000000000013
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation Support Among Children with Adenovirus Infection

Abstract: Overwhelming adenovirus infection requiring extracorporeal membrane oxygenation (ECMO) support carries a high mortality in pediatric patients. The objective of this study was to retrospectively review data from the Extracorporeal Life Support Organization (ELSO) registry for pediatric patients with adenovirus infection and define for this patient cohort: 1) clinical characteristics, 2) survival to hospital discharge, and 3) factors associated with mortality before hospital discharge. In this retrospective regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
3
25
0
4
Order By: Relevance
“…Previous data analysis showed that for children requiring ECMO support for adenovirus infection, the survival rate was only 25% (39), the lowest among the viral types (11,13,31,40), while another review of the Extracorporeal Life Support Organization Registry published in 2014 showed the survival rate at hospital discharge was 38% (41). It was demonstrated that early institution of ECMO in a ventilated patient was associated with improved survival, and late cannulation beyond 6 days was related to an increase in mortality (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Previous data analysis showed that for children requiring ECMO support for adenovirus infection, the survival rate was only 25% (39), the lowest among the viral types (11,13,31,40), while another review of the Extracorporeal Life Support Organization Registry published in 2014 showed the survival rate at hospital discharge was 38% (41). It was demonstrated that early institution of ECMO in a ventilated patient was associated with improved survival, and late cannulation beyond 6 days was related to an increase in mortality (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Low et al (2013) reported three patients with confirmed HAdV-7 ARDS who were treated with VV ECMO; the reported survival rates were poor. Prodhan et al (2014) also reported that only 62 (38.0%) of 163 children with adenovirus pneumonia supported using ECMO survived. However, both of our patients survived throughout the period of ECMO support.…”
Section: Discussionmentioning
confidence: 97%
“…Extracorporeal membrane oxygenation (ECMO) has been used as rescue therapy for patients with severe ARDS caused by HAdV, but the outcome was not satisfactory (Gu et al 2012; Sun et al 2014; Prodhan et al 2014). However, the greatest benefit of ECMO is protecting the lungs from high-pressure mechanical ventilation and oxygen toxicity, minimizing on-going lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…Ancillary measures such as ensuring adequate nutrition, aggressively treating bacterial co-infections, and allowing for viral clearance will optimize the chances at a good outcome. The role of extracorporeal membrane oxygenation support in these children has been associated with poor results [40]. All children with adenoviral pneumonia will require close follow-up upon hospital discharge, given ongoing supportive therapy requirements and the high risk of developing long-term respiratory disease.…”
Section: Adenovirus Pneumoniamentioning
confidence: 99%